Modeling the Colombian Swine Supply Chain from a Knowledge Management Perspective - Trujillo-Diaz, Johanna; Diaz-Piraquive, Flor Nancy; Herrera, Milton M.; Acero, Jairo Gómez (Knowledge Management in Organizations, 2019)
The Colombian swine supply chain (CSSC) has a low level of national competitiveness compared to other supply chains such as coffee and fruit. While consumption of pork has raised in Colombia, most dealers are importing it from The United States and Canada, since farmers in those countries have received agricultural incentives to breed and commercialize pigs. Additionally, agribusiness have received technological developments to share information and develop the swine sector. This article aims to state theoretical Knowledge Management (KM) dimensions for CSSC that were built under authors’ assumptions on the literature. These were proposed to identify the competitiveness level in CSSC, because only two different kinds of measuring for swine competitiveness were found, but on the other hand, no model about Swine Supply Chain (SSC) was found. Perspectives of researching KM in CSSC would integrate stakeholders using a technological web platform which allows interchange of information among them.